Potencial hídrico del suelo en un sistema de cultivo en callejones poró (Erythrina poeppigiana) - frijol (Phaseolus vulgaris) - Jiménez Otárola, Francisco (1997)
The soil water potential was studied at 20 cm depth and at different distances from the tree row (0.5 up 3 m) in a poro-beans alley cropping, in Turrialba, Costa Rica. Tensiometers were installed in direction the trunk of the trees and in direction to the mean distance between the trees towards the cropped alley. No statistically significant differences were found between both positions, but they were found for distance. Near the row of trees and of the zone of direct influence of the crown, water tension was lower; it was higher in the central part of the alley where the crop effect predominated.